Isolation and characterization of the oil oxidizing microorganisms from oil polluted soils of the West Kazakhstan (Eurasian Journal of Ecology, 2016)
We isolated oxidizing microorganisms on developed by us agar medium which contains oil emulgaited by Triton X-100. It was established that oil destruction is carried out by microorganisms consortium but not single species. The study of microorganisms composition consortium showed that there are representatives of the next genera: Bacillus, micromycetes, and yeasts.
Keywords: oil oxidizing microorganisms; consortium; agar medium; emulgator Triton X-100; Bacillus; Micrococcus; micromycetes.